Total Metabolic Syndrome Score in Addition To FIB-4 Score May Be Useful in Predicting Advanced Fibrosis in Metabolic Dysfunction-Associated Steatotic Liver Disease - Gurbuz, Burcu; Koylu, Bahadir; Keskin, Onur (Turkish Journal of Gastroenterology, 2025)
Cite this article as: Gurbuz B, Koylu B, Keskin O. Total metabolic syndrome score in addition to FIB-4 score may be useful in predicting advanced fibrosis in metabolic dysfunction-associated steatotic liver disease. Turk J Gastroenterol. 2025;36(11):796-797.